The Role of STDE Training in Improving Coastal Community Preparedness for Diabetes Emergencies - Merina Widyastuti; Dwi Priyantini; Ninik Ambar Sari; Kukuh Widodo (Universitas STRADA Indonesia, 2026)
Diabetes mellitus is one of the chronic diseases with an increasing prevalence in Indonesia, including in coastal areas. Emergencies due to complications of diabetes, such as hypoglycaemia or hyperglycaemia, are often not handled quickly due to limited public knowledge. Therefore, real efforts are needed to equip the community with basic skills in managing diabetes emergencies. Simple Treatment for Diabetic Emergency (STDE) is one of the educational methods developed by the STIKES Hang Tuah emergency department team to increase knowledge and skills in recognizing the signs and symptoms of hypoglycaemia or hyperglycaemia in patients with diabetes mellitus. This program aims to equip the community with basic skills in handling diabetes mellitus emergencies, including hypoglycaemia and hyperglycaemia conditions. The target of this STDE program is the community of Gisik Gebang Hamlet, Gisik Cemandi, Sedati Sidoarjo as many as 39 people. This activity was carried out for 1 week, which was divided into 3 sessions, namely initial assessment and pre-test, training with simulation, and post-test. The results showed that the average pre-test attitude and knowledge score was 69.18, the average post-test score was 87.3, and with the Wilcoxon statistical test, p < 0.001, there was a difference in attitude and knowledge of the participants before and after STDE training, with an increase of 27.8%. This program is an innovation that coastal communities hope will be able to recognize the early signs of a diabetes emergency and take simple actions that can save lives before advanced medical help is available.